2021
DOI: 10.1001/jamasurg.2021.1642
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Systemic Therapy vs Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy Alone for Resectable Colorectal Peritoneal Metastases

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 34 publications
(44 reference statements)
1
42
2
Order By: Relevance
“…The antivascular endothelial growth factor (VEGF) antibody, bevacizumab, was used (where specifically reported) in 41% (196/480) of patients. 3,12,13,[16][17][18][19] Both the mode and regimen of intraperitoneal chemotherapy varied substantially. Oxaliplatin, mitomycin C, cisplatin, irinotecan, lobaplatin, raltitrexed, and faltitrexed were used in combination or as sole agents as HIPEC.…”
Section: Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The antivascular endothelial growth factor (VEGF) antibody, bevacizumab, was used (where specifically reported) in 41% (196/480) of patients. 3,12,13,[16][17][18][19] Both the mode and regimen of intraperitoneal chemotherapy varied substantially. Oxaliplatin, mitomycin C, cisplatin, irinotecan, lobaplatin, raltitrexed, and faltitrexed were used in combination or as sole agents as HIPEC.…”
Section: Selected Studiesmentioning
confidence: 99%
“…20 Five studies reported on adjuvant systemic chemotherapy by group (NAC versus SF). 12,13,16,19,21 Of these, 46% (164/356) of patients who received NAC also received adjuvant chemotherapy compared with 58% (258/444) of patients who underwent surgery first. Six studies reported on mean/median PCI 12,13,16,19,22,23 and seven studies reported on the completeness of cytoreduction.…”
Section: Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…One trial of note, CAIRO6, seeks to evaluate perioperative systemic chemotherapy and CRS-HIPEC compared to CRS-HIPEC alone in patients with upfront resectable PM. In the Phase II portion of the study, the perioperative chemotherapy regimen appeared safe, although there were similar proportions of macroscopically complete CRS between study arms, perhaps suggesting a lack of benefit of preoperative therapy [ 29 ]. The results of the Phase III portion are eagerly awaited [ 30 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…To address this issue in an RCT, the Dutch CAIRO trial [ 59 ] was initiated in 201 and published in 2021. In their randomized phase 2 trial (combined phase 3 trial), 79 patients were randomized to perioperative systemic therapy (experimental arm) or CRS plus HIPEC alone (control arm, open technique with either mitomycin C (35 mg/m 2 , 90 minutes) or oxaliplatin (460 mg/m 2 , 30 minutes) with intravenous leucovorin (20 mg/m 2 , 10 minutes) and 5-FU (400 mg/m 2 , 15 minutes) according to a local protocol.…”
Section: Neoadjuvant Chemotherapy Before Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapymentioning
confidence: 99%